Adsorption of copper (II) using bamboo leaves ash. - Tuquib, Christian Roy C.
The massive production of bamboo products generates a large volume of leaf wastes that are burned in an uncontrolled manner. Recovery of value added products from the ashes opens a promising path for its economic utilization through its application in adsorption studies. This study was conducted to assess the adsorption behavior towards Cu (II) of bamboo leaves ash (BLA) and a mercaptoacetic acid-modified bamboo leaves ashes (MBLA). The effects of solution pH, initial Cu (II) concentrations, and contact time on adsorption capacity was studied. The parameters generally showed the increase of adsorption capacity when the conditions were increased until saturation was achieved. Equilibrium studies show that adsorption best fit the Langmuir isotherm which indicates a monolayer adsorption. Maximum Cu (II) uptake (q_m) is effective in MBLA, 33.32 ± 0.00 mg g^(-1)capacity, than the BLA, 15.86 ± 0.011 mg g^(-1) capacity.